2016
DOI: 10.1002/jbio.201600146
|View full text |Cite
|
Sign up to set email alerts
|

Structural damage of Bacillus subtilis biofilms using pulsed laser interaction with gold thin films

Abstract: There is a huge interest in developing strategies to effectively eliminate biofilms due to their negative impact in both industrial and clinical settings. In this study, structural damage was induced on two day-old B. subtilis biofilms using the interaction of 532 nm pulsed laser with gold thin films. Radiant exposure of 225 mJ/cm induced distinct changes on the surface structure and overall morphology of the matured biofilms after laser irradiation. Moreover, at the radiant exposure used, changes in the colou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…It is important to note that this technique is different from the more traditional photothermal killing of bacteria, where the combined use of AuNP and laser irradiation kills bacteria by producing heat 31 , 47 , 48 . Despite numerous in vitro studies reporting the effective eradication of biofilms by photothermal treatment 49 54 , translation into clinical practice may be difficult because of heat diffusion into the surrounding healthy tissue 31 , 51 . One study reported on the destruction of Bacillus subtilis biofilms grown on a gold-coated substrate following pulsed laser irradiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that this technique is different from the more traditional photothermal killing of bacteria, where the combined use of AuNP and laser irradiation kills bacteria by producing heat 31 , 47 , 48 . Despite numerous in vitro studies reporting the effective eradication of biofilms by photothermal treatment 49 54 , translation into clinical practice may be difficult because of heat diffusion into the surrounding healthy tissue 31 , 51 . One study reported on the destruction of Bacillus subtilis biofilms grown on a gold-coated substrate following pulsed laser irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…One study reported on the destruction of Bacillus subtilis biofilms grown on a gold-coated substrate following pulsed laser irradiation. Laser irradiation induced localized melting of the gold layer, resulting in the formation of a fast liquid jet and fragmentation of the gold layer 49 . While this affected the biofilm structure, such an approach is limited to applications where biofilms are formed on gold-coated surfaces.…”
Section: Discussionmentioning
confidence: 99%